Tourism and the Refugee issue - Giannoulis, Petros; Kosmas, Petros C. (My University, 2022)
Regardless of the causes of refugee flows, the consequent population displacement brings in a de facto contact different cultural groups (newcomers-host society) with both being influenced by this process. In fact, the main gateways for refugee flows are in many cases areas which are listed as international tourist destinations. Destinations in the Mediterranean Sea such as Turkey, Italy, Greece, Spain, Malta and Cyprus have already accepted and continue to accept thousands of refugees. The same applies for metropolitan areas of the European Union and the United States which have welcomed significant numbers of refugees. Due to the latest developments in economy and public health these tourist destinations face serious challenges. The interaction between the refugee issue and tourism is becoming a research field of key importance because of the resulting economic and social implications and the need to maintain social cohesion in tourist destinations which are becoming refugee host societies. Local integration is a dynamic, two-way process. Refugees must be prepared to adapt to the host communities, while host communities and public institutions who welcome refugees must strive to meet the needs of a diverse population. In this context , tourism may play a crucial role as a social force with the power to contribute to the economies, foster cross-cultural understanding, promote peace, solidarity, development and global consciousness. Utilizing the presence of refugees has the potential to contribute both economically and socially to host societies, provided a holistic approach to managing the influx of refugees is undertaken. The present PhD proposal is an attempt to examine the challenges and opportunities that occur when three “parallel worlds” meet in a tourist destination: host societies, refugees and tourists.